Additive manufacturing of titanium alloys in the biomedical field: processes, properties and applications. Issue 2 (April 2018) - Trevisan, Francesco; Calignano, Flaviana; Aversa, Alberta; Marchese, Giulio; Lombardi, Mariangela; Biamino, Sara; Ugues, Daniele; Manfredi, Diego
The mechanical properties and biocompatibility of titanium alloy medical devices and implants produced by additive manufacturing (AM) technologies – in particular, selective laser melting (SLM), electron beam melting (EBM) and laser metal deposition (LMD) – have been investigated by several researchers demonstrating how these innovative processes are able to fulfil medical requirements for clinical applications. This work reviews the advantages given by these technologies, which include the possibility to create porous complex structures to improve osseointegration and mechanical properties (best match with the modulus of elasticity of local bone), to lower processing costs, to produce custom-made implants according to the data for the patient acquired via computed tomography and to reduce waste.